2022
DOI: 10.3389/fpls.2022.959629
|View full text |Cite
|
Sign up to set email alerts
|

Many paths to one goal: Identifying integrated rice root phenotypes for diverse drought environments

Abstract: Drought is a major source of yield loss in the production of rice (Oryza sativa L.), and cultivars that maintain yield under drought across environments and drought stress scenarios are urgently needed. Root phenotypes directly affect water interception and uptake, so plants with root systems optimized for water uptake under drought would likely exhibit reduced yield loss. Deeper nodal roots that have a low metabolic cost per length (i.e., cheaper roots) via smaller root diameter and/or more aerenchyma and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Changes in plant root system architecture are one of the important measures for plants to cope with abiotic stresses. Under drought stress, plants can effectively enhance drought resistance by increasing root length and changing root structure [ 41 , 42 ]. Recent studies have shown that miR156/SPLs regulate root growth and development in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plant root system architecture are one of the important measures for plants to cope with abiotic stresses. Under drought stress, plants can effectively enhance drought resistance by increasing root length and changing root structure [ 41 , 42 ]. Recent studies have shown that miR156/SPLs regulate root growth and development in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of root loss are context-dependent (83) and may vary for different edaphic conditions. The interaction of CPW with root cortical aerenchyma and root loss merits further exploration to identify optimum integrated phenotypes for specific stresses (40,80,84,85). In silico tools like RootSlice and OpenSimRoot would be useful in exploring highly dimensional fitness landscapes as previously used to test the benefits of cortical cell file number and root cortical aerenchyma in maize (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller and fewer xylem vessels were observed near the rice root apex under drought by Henry et al. (2012) , but other studies observed mixed responses depending on the experiment and the accessions studied ( Fonta et al., 2022a ).…”
Section: Introductionmentioning
confidence: 87%